Pupulation Density Of (Tenualosa ilisha) During The Peak Spawning Season In The Down Stream Barumun River (JURNAL ENGGANO, 2025)
The aim of this study was to explore the population density of (Tenualosa. Ilisha) during its peak spawning season. This understanding is crucial for effective management and conservation of the species, which is critical to fisheries and local ecosystems. The study was conducted from January to April 2023. This period was chosen to capture data during the peak spawning season of Hilsa fish, which is critical for understanding its population dynamics. The study was conducted in the lower reaches of the Barumun River. The study site was divided into three sampling points, which were determined based on information provided by local fishermen. This strategic selection of sampling points was critical to accurately assess the population density of (T. Ilisha) in the river environment. Data analysis in this study utilised SPSS software, Pearson correlation analysis, and focused on key water quality parameters to assess their impact on (T. Ilisha) population density. The population density of (T. Ilisha) was observed to range from 0.11 to 0.14 fish per 100 m² at the station. Correlation analysis showed a strong correlation between salinity and population (0.723). This shows that salinity has the most influence on population density. Based on this it can be concluded that the density of (T.ilisha) fish populations in the lower reaches of the Barumun River is influenced by salinity.